Systematic Literature Review: Faktor Keunggulan Kompetitif Hotel di Indonesia - Ayuk Firdawati; Dwi Cahyono; Gardina Aulin Nuha (Jurnal Akuntansi Terapan dan Bisnis, 2021)
The aim of this research is to identify and evaluate the factors that give hotels in Indonesia a competitive advantage. This research approach is based on a three-stage protocol, which includes an initial stage, implementation, and writing. The initial search string yielded 1,250 journal articles, of which 12 were chosen for further investigation. This study employs qualitative methods, after which the data is extracted and research questions are generated. Differentiation, environmentally friendly technology, service quality, marketing efficiency, market focus, creativity or image, leadership style, information systems, knowledge management, customer intimacy, hotel budgets, and human resources are among the factors that affect hotels' competitive advantage, according to the findings of this report. Both of these factors have a favorable or important impact on hotels' competitive advantage. Originality based on this literature can be seen as a potential research agenda and can aid the growth of the hospitality industry. Keywords: Competitive Advantage, Hotels